Digital media in professional basketball: The case of supporters of the Hamburg Towers - Hodeck, A.; Kerkoski, M. J. (Journal of Human Sport & Exercise, 2019)
Digitalization is one of the global trends. It is relevant to sports and especially to professional sport clubs. As expectations and behaviour of supporters transform, clubs are forced to change their communication strategy to satisfy their customers. This study analyses the media usage and the expectations of supporters of a German professional basketball club. Younger people than in other sports are attracted by basketball, therefore it can be seen as interesting target group. Data (n=285) was collected online and with paper and pencil by using a standardized questionnaire in the season 2018/19. SPSS was used for statistical analysis. Although basketball fans are open minded for new media and use social media more often than others, they still expect traditional communication instruments (as the printed match day programme) from their preferred club. As a consequence, professional sport clubs have to use both traditional and new instruments within their communication strategy.